Breaking Therapeutic Inertia With Alirocumab in an 80-Year-Old Patient With Severe Hypercholesterolemia: A Case Report - Dardano, Angela; Daniele, Giuseppe; Penno, Giuseppe; Miccoli, Roberto; Del Prato, Stefano (Frontiers in Medicine, 2021)
Abstract Background. Therapeutic inertia, defined as the failure to initiate or intensify therapy in a timely manner as per evidence-based clinical guidelines, is an important barrier limiting optimal care in the elderly. Therefore, overcoming therapeutic inertia is the core challenge when dealing with geriatric patients. Case Description. The patient was an 80-year-old man that attended our Outpatient Lipid Clinic (Pisa University Hospital) because of persistent high LDL cholesterol (LDLc) levels in a setting of a statin contraindication. He underwent five percutaneous coronary angioplasties with drug-eluting stents. In 2014, upon starting treatment with rosuvastatin for LDLc level of 7.59 mmol/L, the patient was admitted to the Emergency Room for a presumptive diagnosis of rhabdomyolysis (creatine kinase 6685 U/L) secondary to statin. Patient developed acute kidney injury treated with dialysis. After resolution, he was discharged with ezetimibe (10 mg daily). This treatment however failed to effectively reduce LDLc levels that ranged between 5.9 and 6.6 mmol/L for the ensuing 4-years. In 2018, at the time of our evaluation, in consideration of the age, we performed a comprehensive geriatric assessment that showed good functional and mental status supporting a reliable treatment with a proprotein convertase subtilisin–kexin type 9 inhibitor. Therefore, alirocumab was prescribed as add-on to ezetimibe. At 24-month follow-up, the geriatric assessment showed no significant changes, and alirocumab was well tolerated. LDLc was 82% lower as compared to baseline values (from 6.6 mmol/L to 1.2 mmol/L). Conclusions. This report describes a case of therapeutic inertia despite a very high-risk profile. It is also instrumental in highlightening that appropriate intensification of therapy in an elderly patient at high cardiovascular risk, by means of a patient-centred approach, may allow reaching therapeutic targets and overcoming the condition of therapeutic inertia.